2017
DOI: 10.5152/tao.2017.2077
|View full text |Cite
|
Sign up to set email alerts
|

A New Trend in the Management of Pediatric Deep Neck Abscess: Achievement of the Medical Treatment Alone

Abstract: Objective: We aimed to examine the effect of topical dexamethasone by otomicroscopic and histologic examinations for preventing myringosclerosis induced by myringotomy in rat tympanic membranes.Methods: Twenty-one Sprague Dawley rats (42 ears) were randomly divided into the following three groups after otomicroscopic examinations: experimental surgical group (5 rats), control group (8 rats), and study group (8 rats). The rats of all the groups underwent myringotomy in both tympanic membranes. Other than myring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…ROS can be neutralized by substances with antioxidant properties. There are many studies which show that MS formation can be prevented by applying antioxidant, anti-inflammatory, and ROS scavenging agents ( 1 , 2 , 3 , 4 , 16 , 20 , 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ROS can be neutralized by substances with antioxidant properties. There are many studies which show that MS formation can be prevented by applying antioxidant, anti-inflammatory, and ROS scavenging agents ( 1 , 2 , 3 , 4 , 16 , 20 , 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dündar et al ( 2 ) demonstrated that ascorbic acid and/or N-acetylcysteine treatments reduced the development of MS by reducing inflammation scores and cellular infiltration. Üstündağ et al ( 3 ) found that topical application of dexamethasone in rats after myringotomy has positive effects in reducing both the severity and prevalence of MS. Kargin Kaytez et al ( 4 ) used montelukast orally and topically in rats after myringotomy and reported that it reduced FP and TM thickness. Kazikdas et al ( 20 ) suggested that the prevalence of myringosclerotic plaques was less in rats receiving alpha-tocopherol intramuscularly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas MS is identified histologically in 80% of cases after myringotomy it can be identified under otomicroscopy in only 40% of the cases. This suggests that the actual number of tympanosclerosis cases detected with otomicroscopy could be two-fold ( 6 ). To support this, in a study by Santos et al ( 17 ), the sensitivity and specificity of otomicroscopy was found 80% and 75%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that the incidence of MS was much higher in cases with a history of ventilation tube placement compared to without. These studies also reported the incidence in pediatric patients to range between 28 and 61% ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 93%